Low-cost solution-processed digenite Cu9S5 counter electrode for dye-sensitized solar cells. Issue 61 (7th August 2017) - Hu, Maowei; Yu, Ze; Li, JiaJia; Jiang, Xiaoqing; Lai, Jianbo; Yang, Xichuan; Wang, Mei; Sun, Licheng
Abstract : Cu9 S5 nanocrystalline film is fabricated by a solution-processed method with a low temperature post-treatment at 250 °C and it is further explored as a counter electrode (CE) material in DSSCs. Abstract : The development of low-cost alternatives to the commonly used but expensive platinum (Pt) catalyst in dye-sensitized solar cells (DSSCs) is important from a commercial point of view. In this work, Cu9 S5 nanocrystalline film is fabricated directly onto a F-doped SnO2 (FTO) substrate by a solution-processed spin-coating method with low temperature post-treatment at 250 °C and it is further explored as a counter electrode (CE) material in DSSCs. The results from cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) disclose that Cu9 S5 film exhibits a higher catalytic ability for the state-of-the-art cobalt(ii /iii ) tris(bipyridyl) ([Co(bpy)3 ] 2+/3+ ) redox system as compared to the widely used iodine-based electrolyte. Consequently, the DSSC devices based on the cobalt complex redox shuttles show a power conversion efficiency (PCE) of 5.7% measured at 100 mW cm −2 illumination (AM 1.5G), which is substantially higher than that of the iodine-based counterpart (3.9%). This has been the first presentation for the application of digenite copper sulfides as an electrocatalyst for the [Co(bpy)3 ] 2+/3+ redox system in DSSCs. The present finding represents a promising solution for the development of alternative cost-effective CE materials for DSSCs in the future.